Designing in an indigenous context: zine-making using designerly activity theory to preserve social and local cultural values in Cikondang traditional village - Idhar Resmadi; Ligar Muthmainah; Nisa Eka Nastiti (Institut Seni Indonesia Surakarta, 2025)
This study examines the design of zines as a collaborative medium for preserving the social and cultural values of the Cikondang Traditional Village in Bandung Regency, Indonesia, which only depends on oral transmission of knowledge by the customary leader. Using a qualitative study method and framed by Designerly Activity Theory (DAT), the study collected data through field observations, interviews, focus group discussions, and document analysis. The study identifies key elements of the Designerly Activity Theory (DAT), including subjects and collective subjects, objects in context, tools and signs, rules and design criteria, community and imagined community, and division of labor and process. The urgency of this study lies in developing a zine through a collective and collaborative design system within the context of an indigenous community. The findings indicate that designing zines in indigenous contexts requires heightened attention to community collaboration, the active participation of customary leaders, sensitivity to local ethical and cultural norms, and adherence to community-based design criteria. The study’s primary contribution is the articulation of a systematic design framework that situates zine-making beyond personal expression, foregrounding collaborative, collective, and sociocultural dimensions in the design process. The study contributes to the discourse on participatory and cultural design by positioning Designerly Activity Theory as a critical, analytical, and methodological framework for understanding design as a collaborative, reflective, and culturally embedded activity.